Distribución del género Diplodon (Mollusca:Bivalvia:Hyriidae) en territorio argentino mediante el uso de Colecciones Biológicas - Darrigran, Gustavo (2012)
The pearly freshwater mussels ("naiads") are infaunal species, endemic to the Neotropical region, belonging to the families Hyriidae and Etheriidae. The habitat alteration and competition with the invasive species Corbicula fluminea and Limnoperna fortunei, impact on their natural populations. This communication presents the start of a research project on the geographical distribution of the Diplodon species in Argentina. These species are an important component of the infauna of lotic and lentic water bodies, living in muddy funds, sandy loam, unusually in hard substrate. They are filter feeding, with an important role as recyclers of organic matter. The knowledge of the distribution of the bivalves to the genus Diplodon in Argentine enables the recognition of potential priority areas for conservation. Based on the available literature and on the specimens of the species of the genus Diplodon conserved in the Malacological Collection of the Museo de La Plata (FCNyM -UNLP), a data matrix was made which includes the specimen identification, the collection where it is deposited, the catalog number, locality and date of collection. Each locality was situated by using maps of Argentina and literature reviews, in GoogleEarth satellite imagery, mapping the coordinates for each point. The results give the distribution of native species and discuss the degree of overlap with the two species of bivalve invaders and the impact of human activities.